Emerging Roles of Non-Coding RNA Transcription - Kaikkonen, Minna U.; Adelman, Karen (Trends in biochemical sciences (Amsterdam. Regular ed.), 2018)
Metazoan genomes are broadly transcribed by RNA polymerase II (RNAPII), but surprisingly few of these RNAs encode proteins. Accordingly, there is great interest in understanding the origins and potential roles of the vast array of non-coding RNAs (ncRNAs) that are produced. We present here emerging evidence that the act of transcription and the presence of nascent RNA at a locus is often central to function, rather than specific ncRNA sequences or structures. We highlight examples wherein transcription elongation through a regulatory region modulates chromatin structure and/or transcription factor occupancy, and describe how nascent RNA contributes to the local epigenetic landscape through sequence-independent interactions with chromatin regulators. Finally, we discuss current strategies for probing the potential functions of ncRNA transcription. The location of ncRNAs with respect to target genes is more highly conserved than the ncRNA sequence, suggesting that position-specific cis effects are driving ncRNA evolution. Recent studies indicate that it is often the act of transcription, rather than the sequence or nature of the ncRNA product, that acts as a modulator of chromatin accessibility, transcription factor occupancy, and epigenetic state. Nascent ncRNAs can interact in a sequence-independent manner with epigenetic regulators and transcription factors bound nearby to influence their retention or catalytic activity. Advances in genome-editing and genome-targeting strategies will help to more clearly define the effects of ncRNA transcription on mRNA expression.